Experimental Study on the Ignition Sensitivity and Explosion Severity of Different Ranks of Coal Dust - Junfeng Wang; Xiangbao Meng; Yansong Zhang; Haiyan Chen; Bo Liu (Shock and Vibration)
This study is conducted to examine the ignition sensitivity and explosion severity differences among different ranks of coal dust and reveal the causes underlying these differences. A G–G furnace, a Hartmann tube, and a 20 L explosion tank are used to test MIT, MIE, Pmax, (dp/dt)max, and other parameters of three different ranks of coal dust. SEM analysis is carried out on the coal dust before and after explosion to compare and trace their microstructure changes. The results indicate that the lower the rank of the coal, the more likely the dust cloud to be ignited, the faster the explosion flame propagated, and the greater the explosion severity. The main drivers behind the ignition sensitivity and explosion severity differences among different ranks of coal dust are the volatile content and pyrolytic property of the coal.